The role of interleukins in the progression of liver fibrosis in patients with chronic hepatitis c (Bangladesh Journal of Medical Science, 2026)
Chronic hepatitis C (CHC) remains a major global health burden, affecting approximately 58 million people worldwide and causing nearly 400,000 deaths annually due to complications such as cirrhosis and hepatocellular carcinoma (HCC). According to the World Health Organization. Progressive liver fibrosis is a central mechanism leading to these adverse outcomes and significantly reduces patients’ quality of life. Interleukins play a crucial role in the inflammatory and fibrogenic processes associated with HCV infection. Proinflammatory cytokines, including IL-6, IL-1β, and TNF-α, contribute to hepatic stellate cell activation and collagen deposition, promoting fibrosis progression. Elevated levels of these cytokines have been shown to correlate with fibrosis severity. Recent studies also highlight the role of IL-33, IL-17, IL-25, and IL-1α as potential biomarkers of liver damage. Understanding cytokine-mediated mechanisms of fibrogenesis may improve early diagnosis, prognosis, and targeted therapeutic strategies in CHC patients.BJMS, Vol. 25 No. 02 April’26 Page: 583-590